2016
DOI: 10.1242/jeb.136101
|View full text |Cite
|
Sign up to set email alerts
|

Urchins in a high CO2 world: partitioned effects of body-size, ocean warming and acidification on metabolic rate

Abstract: Body size and temperature are the major factors explaining metabolic rate, and the additional factor of pH is a major driver at the biochemical level. These three factors have frequently been found to interact, complicating the formulation of broad models predicting metabolic rates and hence ecological functioning. In this first study of the effects of warming and ocean acidification, and their potential interaction, on metabolic rate across a broad range in body size (two to three orders of magnitude differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 72 publications
(114 reference statements)
1
49
2
Order By: Relevance
“…Additionally, we performed the feeding experiments only with the sea urchin P. lividus , whereas different herbivore species may have responded differently to CO 2 -driven changes in plant chemical composition4574 or epiphyte abundance or composition since it is expected that fleshy epiphytes may increase93 and calcareous epibionts would decrease their abundance under low pH conditions30. While we only performed the feeding experiments under ambient CO 2 water conditions, studies to date with adult sea urchins do not suggest strong changes in feeding rates9495, nor in preferences (S.R. Fitzpatrick, personal communication) under ambient vs. high p CO 2 conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we performed the feeding experiments only with the sea urchin P. lividus , whereas different herbivore species may have responded differently to CO 2 -driven changes in plant chemical composition4574 or epiphyte abundance or composition since it is expected that fleshy epiphytes may increase93 and calcareous epibionts would decrease their abundance under low pH conditions30. While we only performed the feeding experiments under ambient CO 2 water conditions, studies to date with adult sea urchins do not suggest strong changes in feeding rates9495, nor in preferences (S.R. Fitzpatrick, personal communication) under ambient vs. high p CO 2 conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This can either be in the form of lower seawater pH reducing thermal tolerance and narrowing thermal windows (as in Metzger et al ., ; Walther et al ., ), or alternatively, warming may counteract effects of reduced pH through stimulation of metabolic rates (as in Byrne et al ., ; Sheppard Brennand et al ., ). Furthermore, it is possible that the metabolic costs associated with the stressors may be additive (Byrne, ; Carey et al ., ). Among these outcomes, the present study found that for all the developmental stages and species examined, the effect of pH on thermal windows was additive, with increased abnormality and growth reductions under reduced pH being consistent across thermal gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in a recent study on the effects of warming and reduced pH on metabolic rates of juvenile and adult Heliocidaris erythrogramma (Carey et al ., ) in which urchins were exposed to two temperature treatments (18 °C and 23 °C) and two pH treatments (7.5 and 8.0) for a period of 2 months. Thermal stress incurred a 20% increase on the metabolic rate, while reduced pH increased the metabolic rate by 19%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sea urchins exhibit considerable capacity to adjust the acid−base balance of their coelomic fluid in response to increased acidification and thus can maintain body fluid homeostasis , although living with increased acidification incurs an energetic cost (Carey et al 2016). It may be that spines, teeth and test plates, although lower in Mg and thus less soluble, will prove to be more vulnerable to dissolution effects.…”
Section: Environmental Patterns and Ocean Acidificationmentioning
confidence: 99%